Records management : - Ashe, Carolyn (PearsonPrentice Hall, 2004)
This book provides in-depth coverage of current issues in records and information management(RIM)—topics that are of interest and concern to professionals in the field. Its focus on the twenty-first century considers past, current, and future records and information trends substantiating the need for assurance that information will be found or available at the right place and/or time. Some of the many topics addressed include concern for ethical and legal practices, technology, storage, retrieval, and disaster recovery. For records managers, records and information managers, and information managers; as well as those seeking certification (Editorial Reviews)